Experience of gender-based violence among high school-going youth in Estcourt, KwaZulu-Natal - Thobile B. Mchunu; Nelisiwe Khuzwayo (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Gender-based violence (GBV) is a global public health issue, particularly affecting women and vulnerable youth, with an estimated 150 million girls and 73 million boys impacted worldwide. GBV can negatively impact the academic attainment of learners.